Misery Loves Company: An Investigation of Couples’ Interrole Conflict Congruence - Wilson, Kelly Schwind; Baumann, Heidi M.; Matta, Fadel K.; Ilies, Remus; Kossek, Ellen Ernst (Academy of Management Journal, 2018)
Previous research on interrole (family-to-work and work-to-family) conflict has demonstrated that such conflict is detrimental for outcomes in the work and home domains for employees and their family members. Although research has begun to integrate multiple parties into the interrole conflict literature, studies have overlooked how employee interrole conflict and partner interrole conflict can jointly influence employee outcomes. We advance work–family research by integrating balance theory with the interrole conflict literature to investigate dyadic interrole conflict congruence and challenge the implicit assumption that less interrole conflict always results in superior outcomes. Using a polynomial regression analysis of 141 employee and romantic partner dyads, we demonstrate that congruence between couples’ experiences of family-to-work (but not work-to-family) conflict is positively associated with balance satisfaction, and ultimately employee job satisfaction and partner relationship satisfaction. Thus, when it comes to balance satisfaction and its downstream correlates, the harmful effects of high family-to-work conflict (FWC) are largely mitigated if an employee’s partner shares a similarly high level of FWC, and the beneficial effects of low FWC are largely eliminated if an employee’s partner does not share a similarly low level of FWC.